'Treatable and Changeable': The Effect of Treatment and Malleability Information on Stigma Towards Children with Behavioural Problems and Their Parents. Issue 4 (2nd December 2020) - Li, Sarah; Tully, Lucy; Dadds, Mark R.
Abstract: Improving knowledge about childhood mental health issues, reducing stigma, and encouraging appropriate treatment-seeking are important goals for public health. This study examined the effect of treatment and malleability information on stigmatisation towards children with Oppositional Defiant Disorder (ODD) and their parents, and on endorsements of causal beliefs. In an experimental study, university students ( N = 234) were randomly allocated to receive/not receive treatment information (information on the existence and effectiveness of treatment for ODD) and to receive/not receive malleability information (information emphasising brain malleability and the potential to change). Participants then rated four measures of stigma towards a fictitious child with ODD and mother (blame, incompetence, dangerousness, and social distance), and rated their endorsements of causal explanations for ODD. Neither treatment nor malleability information had significant effects on stigmatisation towards either the child or mother. However, this information did impact upon causal beliefs about ODD as stemming from biological or mixed biological/environmental causes. Implications for the future development of public health initiatives and stigma research on childhood mental health are discussed.